Inferior survival for patients with malignant peripheral nerve sheath tumors defined by aberrant TP53. (November 2018) - Høland, Maren; Kolberg, Matthias; Danielsen, Stine; Bjerkehagen, Bodil; Eilertsen, Ina; Hektoen, Merete; Mandahl, Nils; van den Berg, Eva; Smeland, Sigbjørn; Mertens, Fredrik; Sundby Hall, Kirsten; Picci, Piero; et al.
Abstract Malignant peripheral nerve sheath tumor is a rare and aggressive disease with poor treatment response, mainly affecting adolescents and young adults. Few molecular biomarkers are used in the management of this cancer type, and althoughTP53 is one of few recurrently mutated genes in malignant peripheral nerve sheath tumor, the mutation prevalence and the corresponding clinical value of the TP53 network remains unsettled. We present a multi-level molecular study focused on aberrations in the TP53 network in relation to patient outcome in a series of malignant peripheral nerve sheath tumors from 100 patients and 38 neurofibromas, includingTP53 sequencing, high-resolution copy number analyses ofTP53 andMDM2, and gene expression profiling. Point mutations inTP53 were accompanied by loss of heterozygosity, resulting in complete loss of protein function in 8.2% of the malignant peripheral nerve sheath tumors. Another 5.5% hadMDM2 amplification.TP53 mutation andMDM2 amplification were mutually exclusive and patients with either type of aberration in their tumor had a worse prognosis, compared to those without (hazard ratio for 5-year disease-specific survival 3.5, 95% confidence interval 1.78–6.98). Both aberrations had similar consequences on the gene expression level, as analyzed by aTP53 -associated gene signature, a property also shared with the copy number aberrations and/or loss of heterozygosity at theTP53 locus, suggesting a common "TP53 -mutated phenotype" in as many as 60% of the tumors. This was a poor prognostic phenotype (hazard ratio = 4.1, confidence interval:1.7–9.8), thus revealing aTP53 -non-aberrant patient subgroup with a favorable outcome. The frequency of the "TP53 -mutated phenotype" warrants explorative studies of stratified treatment strategies in malignant peripheral nerve sheath tumor.